(3GdMdbGJ, GdMdbjGJ hGdLHQ GdNWj (B/s - (3gGQJdj, Hs; (3J, gGhcSs ((3GdQjGV(B: s (3LGeYI Gdedc SYhO(B, s, 1999)
(3GdMdbGJ hGdMdbjGJ(B- (3GdMdbGJ GdLRFjI hGdJTcjdGJ hGdeKGdjGJ(B- (3HfGA MdbGJ LOjOI(B- (3GdJMdjd aj GdMdbGJ GdJGeI(B- (3GdMdbjGJ GdNGUI(B- (3GdJaQjb GdeHGTQ ddMdbjI ehdOI fgGFjG Ydi MdbI JGeI QFjSjI(B- (3GdMdbGJ GdLRFjI ef GdMdbjGJ GdMQI(B- (3eHQgfGJ GdJaQjb(B- (3ebGQfI dG JYJeO Ydi GdeUahaGJ(B- (3JWHjbGJ Ydi GdReQ hGdeUahaGJ(B- (3GdReQI GdehdOI fgGFjG(B- (3GdJMhjdGJ GdNWjI hGdeUahaGJ hGdCTcGd GdbGfhfjI(B- (3MSGH GdGTcGd GdbGfhfjI(B.s
Keywords: (3GdLHQs; (3GdQjGVjGJs